RELATIONSHIP BETWEEN DENTAL HYGIENE PERCEPTION AND OHI-S STATUS IN MALOCCLUSION STUDENTS AT POLTEKKES KEMENKES ACEH - Mauliana, Mauliana; Reca, Reca (UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Background: The prevalence of individuals with dental and oral problems in Aceh is 55.34%. One of the reasons someone neglects their dental and oral health issues is the poor perception of dental and oral hygiene maintenance. Malocclusion problems can exacerbate dental and oral hygiene conditions (OHI-S), hence the need for educational intervention for the community, especially students. Objective: To determine the relationship between the perception of dental and oral hygiene maintenance and OHI-S status in students with malocclusion in the Department of Nutrition at Poltekkes Kemenkes Aceh. Method: This study is analytical with a cross-sectional design conducted on 69 students from the Department of Nutrition at Poltekkes Kemenkes Aceh. Students were examined for their OHI-S dental status and given a questionnaire about the perception of dental and oral hygiene; the sample selection criteria involved students with dental malocclusion. Instruments used: diagnostic tools set, KSP OHI-S, and questionnaires. Results: The research shows that students with a good perception of oral hygiene maintenance dominate with a good OHI-S status, amounting to 22 (51.2%). Based on statistical test results, there is a relationship between the perception of oral hygiene maintenance and OHI-S status p=0.001 (p<0.05). Conclusion: It can be concluded that the perception of oral hygiene influences the OHI-S status in patients with dental malocclusion.